Revision of the EU-legislation on the marketing and use of feed with particular focus on nutrition of horses - Trunk, Wolfgang (MTT, 2008)
Currently, the general rules for the marketing of feed are spread over several Directives according to the type of feed concerned. There is Directive 79/373/EEC on compound feed covering also pet food where the rules for the circulation of this feed in the EU are laid down (e.g. labelling requirements). Directive 93/74/EEC lays down the principles for feedingstuffs intended for particular nutritional purposes ( dietetic feeds ). Directive 96/25/EC contains the general rules for the circulation and use of feed materials. Directive 82/471/EEC lays down the marketing conditions for certain products, belonging to the category feed materials, used in animal nutrition ( bio-proteins ). Thus, the current rules are found in old Directives and some 50 amending or implementing acts. This has made existing legislation extremely scattered with many cross references and difficult to understand and implement in a uniform way. Feed legislation sets the rules for the different categories as of feed materials, dietetic feed, feed additives and medicated feed, differentiating between food producing animals and pets. Though horses might not be used for food production in all cases, feed legislation has to consider them as food producing animals because they enter to a significant extent the food chain. The main improvement of the proposal will be achieved by setting modern rules under one Regulation resulting in more legal clarity and a more homogenous market. In particular, the grey zone between feed materials, feed additives and veterinary drugs would be cleared. Further, the use of claims will be better regulated and thus enforceable for the control authorities. On feed intended for particular nutritional purposes, the current system will be more or less retained. The proposal introduces a broad definition of labelling. Consequently, the required truthfulness of the information attributed to a product is not only limited to the sack label but as well to all other material supporting the sale. Additionally, it is highlighted that sales via the internet are covered by the marketing rules. Furthermore, proposal increases the accuracy of the indication of feed materials incorporated in compound feed for food producing animals by requiring the indication in descending order of weight. The exact percentage has to be indicated for raw materials in compound feed that are highlighted on the label. The proposal follows the philosophy that information needed by the feed user for an informed choice and safety relevant information must be provided unequivocally and in a harmonised way throughout the Community. Further labelling particulars can be given on a voluntary basis to fulfil special interest of customers, but then these have to be accurate and understandable for each target group, and the industry could label all details voluntarily. Stakeholders will be encouraged to develop EU codes for good labelling practice in the context of voluntary labelling provisions. The proposal is now in negotiation in the Council of the EU and the European Parliament for adoption.
Keywords: Ko; EU-legislation; feeds; marketing; horse